Diatom diversity and seasonality in two rivers in Serbia - Vidaković, Danijela; Ćirić, Miloš; Krizmanić, Jelena (Macedonian Journal of Ecology and Environment, 2020)
During the four seasons of investigation in the Rača and Studenica rivers (spring 2011, summer 2011, winter 2011 and spring 2012) 171 and 190 epilithic diatoms were recorded, respectively. The most numerous genera in both rivers were Gomphonema, Navicula, and Nitzschia. Of total recorded taxa 11 are new for the diatom flora of Serbia. The highest species diversity was in spring, while the lowest was during the summer and winter periods. In almost all seasons Cocconeis lineata occurred with the highest frequencies in the Rača River. In the Studenica River epilithic diatom community was dominated by Achnanthidium pyrenaicum, except in winter 2011 and spring 2012 when Diatoma moniliformis and Gomphonema species were the most abundant diatoms, respectively. The regular pattern of diatom succession was not recorded in two investigated rivers.